2017
DOI: 10.1002/jhet.2990
|View full text |Cite
|
Sign up to set email alerts
|

3‐(2‐(2‐Oxo‐2H‐chromene‐3‐carbonyl)hydrazono)‐N‐(pyridin‐2‐yl)butanamide Complexes: Synthesis, Characterization, DFT, Biological, and Ion‐flotation studies

Abstract: Schiff base complexes of Cu(II), Ni(II), Cd(II), and Zn(II) with 3‐(2‐(2‐oxo‐2H‐chromene‐3‐carbonyl)hydrazono)‐N‐(pyridin‐2‐yl)butanamide (H2L) were produced. The synthesized compounds were deduced by elemental analysis, molar conductance, magnetic susceptibility, and spectroscopic techniques. The geometry of the prepared complexes was estimated by applying DFT method. Also, Cu(II) and Zn(II) were separated using a simple, quick, and low‐cost quantitative flotation technique preceding to their determinations u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In this paper, the chemical properties of TPA + were analyzed at the atomic level using DFT to provide further insight into the interaction mechanism of the collector. A commonly used visual method to observe the electron distribution of molecules is the MEP . The HOMO and LUMO geometries of the analyzed TPA molecule after optimization and the MEP maps are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, the chemical properties of TPA + were analyzed at the atomic level using DFT to provide further insight into the interaction mechanism of the collector. A commonly used visual method to observe the electron distribution of molecules is the MEP . The HOMO and LUMO geometries of the analyzed TPA molecule after optimization and the MEP maps are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…42−44 A commonly used visual method to observe the electron distribution of molecules is the MEP. 45 The HOMO and LUMO geometries of the analyzed TPA molecule after optimization and the MEP maps are shown in Figure 12. The net atomic charge results obtained after the calculation are arranged in Table 1.…”
Section: Contact Angle Testsmentioning
confidence: 99%
“…The MEP maps of DPA + and DA + are illustrated in Figure c. MEP is an intuitive method of looking at the electron distribution of a molecule . The blue color of map represents the negatively electrostatic potential, which is a favor site for electrophilic attack, and the red color of map represents the positive electrostatic potential, which is a favor site for nucleophilic attack.…”
Section: Resultsmentioning
confidence: 99%
“…MEP is an intuitive method of looking at the electron distribution of a molecule. 52 The blue color of map represents the negatively electrostatic potential, which is a favor site for electrophilic attack, and the red color of map represents the positive electrostatic potential, which is a favor site for nucleophilic attack. It is demonstrated that two deeper blue regions of DPA than DA were located on the −CH 2 NH-(CH 2 ) 2 C(NOH)N + H 3 group.…”
Section: ■ Introductionmentioning
confidence: 99%